PENERAPAN CONTEXTUAL TEACHING AND LEARNING DENGAN NUMBERED HEADS TOGETHER UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Supriyanto Supriyanto; Sunarto Sunarto; Sudarno Sudarno (BISE: Jurnal Pendidikan Bisnis dan Ekonomi, 2017)
The objective of this research is to improve students’ learning outcomes in doing confirmation of customer’s decision through the implementation of the Contextual Teaching and Learning with Cooperative Learning of Number Heads Together at State Vocational High School 1 Sukoharjo in Academic Year 2015/2016.  The subject of the research was the students of class XI Marketing 2 at State Vocational High School 1 Sukoharjo. It consisted of 34 students. Data sources of the research were taken from teacher, students, and documents. Techniques of collecting data used were interview, observation, and documentations. In this study, data validity test is done by triangulation of sources. Data analysis techniques with comparative descriptive data analysis, quantitative and qualitative dataThe result of the research showed that there was significant learning outcomes improvement from pre-cycle to cycle I and continued to cycle II. This result showed that the percentage of students who can reach passing grade of the last learning outcomes was 64,70 % or 22 students. Contextual Teaching and Learning with Numbered Head Together was implemented in cycle I and the percentage of students’ learning outcomes improved. The percentage was 79,41% or 27 students. The improvement also happened in cycle II. The percentage of students’ learning outcomes became 85,29% or 29 students.